ANALYSIS OF CRITICAL THINKING OF PROSPECTIVE MATHEMATICS TEACHERS IN SOLVING ASSESSMENT PROBLEMS - Dewi Sukriah; Dwi Juniati (USN Kolaka, 2023)
Professional teacher candidates must have several competencies, including pedagogical competence. This competency is essential to understand the characteristics of students in various aspects. Simple qualitative descriptive research that describes the critical thinking skills of prospective mathematics teachers based on the percentage of achievement of critical thinking skills test results. We researched 6th-semester students of the Mathematics Education Study Program consisting of 35 students. The research instrument used critical thinking skills test questions consisting of 5 questions prepared based onindicators of critical thinking skills: identifying and interpreting, analyzing, evaluating, connecting, and solving problems. Data analysis used a percentage system. The results showed that the critical thinking skills of prospective mathematics teachers had a total average of 70% in the high category. This result is supported by the percentage of critical thinking skills in eachindicator: interpreting and identifying indicators by 85%, analyzing indicators by 70%, connecting indicators by 82.14%, problem-solving indicators by 20%, and evaluating indicators by 92.86%. The results of the percentage classified by gender show that the ability of female prospective mathematics teachers to think critically on each indicator is better than that of male prospective mathematics teachers.